Horizon entropy with loop quantum gravity methods - Sahlmann, Hanno; Pranzetti, Daniele (Physics Letters B, 2015)
We show that the spherically symmetric isolated horizon can be described in terms of an SU(2) connection and an su(2)-valued one-form, obeying certain constraints. The horizon symplectic structure is precisely the one of 3d gravity in a first order formulation. We quantize the horizon degrees of freedom in the framework of loop quantum gravity, with methods recently developed for 3d gravity with non-vanishing cosmological constant. Bulk excitations ending on the horizon act very similarly to particles in 3d gravity. The Bekenstein-Hawking law is recovered in the limit of imaginary Barbero-Immirzi parameter. Alternative methods of quantization are also discussed.